IMPACT OF HEAT STRESS ON OVARIAN FOLLICLE DEVELOPMENT AND DYNAMICS IN LARGE RUMINANTS (The Research of Medical Science Review, 2025)
Heat stress is a major environmental stressor that adversely affects the reproductive performance of livestock, particularly large ruminants. As global temperatures continue to rise, understanding the physiological effects of heat stress on ovarian follicle growth and reproductive health is crucial for improving fertility in ruminant herds. This study aimed to examine the effects of heat stress on ovarian follicle development, estradiol concentrations, and oocyte quality in large ruminants, particularly cattle, in regulated environmental settings. A comparative experimental design was used at University of Veterinary and Animal Sciences, Lahore, Pakistan, involving 30 mature female cattle categorized into heat-stressed and control groups. The heat-stress group was exposed to extreme temperatures (35-38°C) for 12 h each day over a duration of 4 weeks. Ovarian follicle dimensions and dynamics were observed via ultrasonography, and hormonal profiles (estradiol and progesterone) were evaluated using blood samples obtained biweekly. Statistical analysis was performed using t-tests to assess follicle size and hormone levels between groups. The findings indicated that heat stress markedly diminished ovarian follicle size and estradiol levels in the heat-stressed group compared to the control group (p = 0.017 for follicle size, p = 0.0017 for estradiol). No significant difference was observed in progesterone levels between the two groups (p = 0.0888). These data indicate that heat stress predominantly impacts the initial phases of follicular growth and estradiol production. This study offers significant insights into the detrimental effects of heat stress on ovarian follicle growth and estradiol regulation in large ruminants. These results underscore the necessity of implementing efficient heat stress mitigation measures in cattle management to maintain reproductive health and improve fertility in heat-impacted areas.